Application of Fourier transform infrared spectroscopy (FTIR) for protozoan analysis: A systematic review - Juan Felipe Ramirez Giraldo; Jorge Enrique Gomez Marin (Photodiagnosis and Photodynamic Therapy)
Summary: Protozoa present in water for human consumption represent a significant public health risk to a greater extent in the most vulnerable populations. Identifying protozoa in a traditional way through microscopy or with more advanced technologies such as molecular biology may present limitations in sensitivity, specificity, time, and costs. Fourier Transform Infrared (FTIR) spectroscopy have potential as an alternative for the detection of protozoa in water used for human consumption. An exhaustive search was carried out in the databases, SCIELO, PubMed, SCOPUS and Google Scholar, with the search terms “protozoa,” “protozoan,” “parasite,” “FTIR,” “infrared spectroscopy.” Only six articles met the inclusion criteria. FTIR spectroscopy can detect changes in biochemical composition but has not been used for the identification of parasites in human clinical or environmental samples. The present systematic review identified a lack of studies in this area and the need to conduct research aimed at developing standardized methods and creating spectral database banks of protozoan species that will allow for the precise identification of protozoa such as Cryptosporidium spp. and Giardia spp. in water for human consumption.